1991
DOI: 10.1111/j.1440-1681.1991.tb01421.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Macula Densa in Renin Synthesis

Abstract: 1. The role of the macula densa in renin synthesis was studied using mice with one hydronephrotic kidney. 2. Renin synthesis was assessed by measurement of renal renin, renal mRNA for renin and plasma renin. 3. Sodium depletion stimulated mRNA and renal renin to a similar extent in the hydronephrotic and contralateral kidney. 4. Enalapril stimulated mRNA concentration in both kidneys but renal renin did not rise in the hydronephrotic kidney. 5. Propranolol did not alter the response to sodium depletion in eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Thus, in mice and rats with one hydronephrotic, nonfiltering kidney with severe tubular atrophy, the renal renin mRNA and protein levels were normally regulated in the filtering and nonfiltering kidneys by high and low salt diets [83,107,126,128]. Interestingly however, the renin release from the hydronephrotic kidney did not change in parallel to the renin synthesis, as was the case in the healthy contralateral kidney [127,128]; this result indicated that the macula densa might play a role in the proper renin release in this situation.…”
Section: The Macula Densa Mechanismmentioning
confidence: 94%
“…Thus, in mice and rats with one hydronephrotic, nonfiltering kidney with severe tubular atrophy, the renal renin mRNA and protein levels were normally regulated in the filtering and nonfiltering kidneys by high and low salt diets [83,107,126,128]. Interestingly however, the renin release from the hydronephrotic kidney did not change in parallel to the renin synthesis, as was the case in the healthy contralateral kidney [127,128]; this result indicated that the macula densa might play a role in the proper renin release in this situation.…”
Section: The Macula Densa Mechanismmentioning
confidence: 94%